Fluid flow handbook (McGraw-Hill, 2002)
The most comprehensive reference available on this topic, Fluid Flow Handbook skillfully blends theoretical review and engineering practicality. The author, expert Jamal Saleh, provides a balanced, detailed, and extensive treatment of pumps, pipes and piping systems, hydraulics, hydrology, and more. Well-illustrated, and completely up-to-date, the Handbook offers: Discussion of issues critical to civil engineers, including flow in open channel, flow meters in rivers, and discharge from hydraulic structures, Integration between physical properties, thermodynamics and heat transfer into fluid flow analysis, Numerous applications from petroleum distribution, piping flow, valves, and other fittings,...